Shooting may aggravate rather than alleviate conflicts between migratory geese and agriculture. Issue 6 (15th April 2018) - Bauer, Silke; Lisovski, Simeon; Eikelenboom‐Kil, Ramona J. F. M.; Shariati, Mitra; Nolet, Bart A.
Abstract: Many migratory goose populations have thrived over the past decades and their reliance on agricultural resources has often led to conflicts. Control and management measures are sought after but since migratory geese use several sites in their annual cycle, local management actions should consider their potential effects further down the flyway. We used a behaviour‐based migration model to illustrate the consequences of management actions involving hunting, derogation shooting and scaring at single or multiple locations along the flyway, considering various mechanisms of how geese might perceive shooting/hunting. Furthermore, as a proxy for the agricultural damage caused, we calculated the per capita biomass consumption between scenarios—both over time and cumulatively. We found that hunting, shooting and scaring can result in a suite of direct and indirect consequences on migration and foraging behaviour. Most importantly, hunting/shooting on a particular site had implications not only for the behaviour at the actual site but also for behaviour at, and use of, other sites. Furthermore, the specific consequences of shooting/hunting could be counter‐intuitive, that is, aggravate rather than alleviate agricultural damage, depending on where along the migration route changes had taken place and the mechanisms through which hunting/shooting was assumed to affect geese. Synthesis and applications . Management plans are being discussed or implemented for several migratory goose populations and often include shooting, hunting or scaring at one or multiple locations. Using a behaviour‐based model, we assessed the consequences of such local management measures and found that they can indeed lead to a reduction of agricultural conflicts locally but may also aggravate the conflict or shift it to other sites along the flyway. Thus, we recommend the use of these models to scrutinize the efficiency of specific management measures and to assist in identifying an international management regime that minimizes conflicts on a flyway level while still maintaining migratory populations. Abstract : Management plans are being discussed or implemented for several migratory goose populations and often include shooting, hunting or scaring at one or multiple locations. Using a behaviour‐based model, we assessed the consequences of such local management measures and found that they can indeed lead to a reduction of agricultural conflicts locally but may also aggravate the conflict or shift it to other sites along the flyway. Thus, we recommend the use of these models to scrutinize the efficiency of specific management measures and to assist in identifying an international management regime that minimizes conflicts on a flyway level while still maintaining migratory populations.